Exit and Entry, Increasing Returns to Specialization, and Business Cycles - Michael B. Devereux; Allen C. Head; Beverly J. Lapham (Queen's University, Department of Economics, 1993)
The effects of entry and exit by monopolistically competitive intermediate goods producers on equilibrium business cycles are analyzed in the presence of internal returns to scale and external returns to specialization. In the environment studied, market power and endogenous entry and exit, in themselves, have little effect on the propagation of technology shocks. In contrast, internal returns to scale dampen the effects of these shocks while external returns to specialization produce a multiplier which accentuates their effects. The multiplier arises as entry and exit of firms over the business cycle causes endogenous fluctuations in the productivity of intermediate inputs. These endogenous productivity fluctuations cause the Solow residual both to mismeasure technology shocks and to be strongly correlated with government spending shocks. The results also indicate that the extent to which technology shock can account for aggregate fluctuations may be greater than suggested by competitive real business cycle models.
Keywords: E32; 330